Operation and Governance of the National Health System of Ecuador - Molina Guzmán, Adriano (2019)
The National Health System of Ecuador (SNS) is characterized by its segmentation and fragmentation, which limits the implementation of public policies in the sector and provisional services. This study was conducted using an analytical framework of governance in health and observations of the type of principal-agent relations in the provision of public services. It is based on a case study that shows how the institutional configuration of SNS in Ecuador unfolds and how this affects the implementation of public policies. The results show that despite the designed mechanisms in place to improve the coordination of the health system, the institutional structure hinders the implementation of integrated networks of provision services